Hyperfractionated stereotactic reirradiation for recurrent head and neck cancer - Cvek, Jakub; Knybel, Lukas; Skacelikova, Eva; Stransky, Jiri; Matousek, Petr; Zelenik, Karol; Res, Oldrich; Otahal, Bretislav; Molenda, Lukas; Feltl, David (Strahlentherapie und Onkologie, 2016)
PURPOSE: The goal of this work was to evaluate the efficacy and toxicity of hyperfractionated stereotactic reirradiation (re-RT) as a treatment for inoperable, recurrent, or second primary head and neck squamous cell cancer (HNSCC) that is not suitable for systemic treatment. PATIENTS AND MATERIALS: Forty patients with recurrent or second primary HNSCC were included in this study. The patients had a median gross tumor volume of 76 ml (range 14-193 ml) and a previous radiotherapy dose greater than 60 Gy. Treatment was designed to cover 95 % of the planning target volume (PTV, defined as gross tumor volume [GTV] + 3 mm to account for microscopic spreading, with no additional set-up margin) with the prescribed dose (48 Gy in 16 fractions b.i.d.). Treatment was administered twice daily with a minimum 6 h gap. Uninvolved lymph nodes were not irradiated. RESULTS: Treatment was completed as planned for all patients (with median duration of 11 days, range 9-14 days). Acute toxicity was evaluated using the RTOG/EORTC scale. A 37 % incidence of grade 3 mucositis was observed, with recovery time of ≤ 4 weeks for all of these patients. Acute skin toxicity was never observed to be higher than grade 2. Late toxicity was also evaluated according to the RTOG/EORTC scale. Mandible radionecrosis was seen in 4 cases (10 %); however, neither carotid blowout syndrome nor other grade 4 late toxicity occurred. One-year overall survival (OS) and local progression-free survival (L-PFS) were found to be 33 and 44 %, respectively. Performance status and GTV proved to be significant prognostic factors regarding local control and survival. CONCLUSION: Hyperfractionated stereotactic re-RT is a reasonable treatment option for patients with recurrent/second primary HNSCC who were previously exposed to high-dose irradiation and who are not candidates for systemic treatment or hypofractionation.
Keywords: Otorhinolaryngologic Neoplasms; Humans; Squamous cell carcinoma of the head and neck; lidé středního věku; Disease Progression; otorinolaryngologické nádory; Female; Aged; dospělí; Neoplasms, Second Primary; senioři; lidé; Overall survival; Toxicity; Retreatment; radiochirurgie; Adult; Postoperative Complications; sekundární malignity; Radiosurgery; Reirradiation; staging nádorů; pooperační komplikace; ženské pohlaví; Male; Middle Aged; Aged, 80 and over; senioři nad 80 let; progrese nemoci; spinocelulární karcinom; Carcinoma, Squamous Cell; Neoplasm Staging; lokální recidiva nádoru; míra přežití; mužské pohlaví; Neoplasm Recurrence, Local; Stereotactic radiotherapy; opakovaná terapie; Survival Rate